2020
DOI: 10.21037/tlcr-20-522
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-mesenchymal transition is a resistance mechanism to sequential MET-TKI treatment of MET-amplified EGFR-TKI resistant non-small cell lung cancer cells

Abstract: Background: Tyrosine kinase inhibitor (TKI) resistance is a major obstacle in treatment of non-small cell lung cancer (NSCLC). MET amplification drives resistance to EGFR-TKIs in 5-20% of initially sensitive EGFR-mutated NSCLC patients, and combined treatment with EGFR-TKIs and MET-TKIs can overcome this resistance. Yet, inevitably MET-TKI resistance will also occur. Hence, knowledge on development of this sequential resistance is important for identifying the proper next step in treatment.Methods: To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The function of individual inhibitors was validated as shown in Figure S10 . Blocking HGF with capmatinib, an ATP-competitive inhibitor of c-MET ( Clement et al, 2020 ; Kong et al, 2020 ; Oh et al, 2021 ), while dramatically reducing organoid size, had a moderate impact on colony-forming efficiency (CFE) ( Figure 6A , a8 and a9 ). Inhibition of BMP by GREM2 ( Tanwar et al, 2014 ) had no impact on CFE but reduced the organoid size, suggesting its activity may be more related to pAT2 proliferation ( Figure 6A , a8 and a9 ).…”
Section: Resultsmentioning
confidence: 99%
“…The function of individual inhibitors was validated as shown in Figure S10 . Blocking HGF with capmatinib, an ATP-competitive inhibitor of c-MET ( Clement et al, 2020 ; Kong et al, 2020 ; Oh et al, 2021 ), while dramatically reducing organoid size, had a moderate impact on colony-forming efficiency (CFE) ( Figure 6A , a8 and a9 ). Inhibition of BMP by GREM2 ( Tanwar et al, 2014 ) had no impact on CFE but reduced the organoid size, suggesting its activity may be more related to pAT2 proliferation ( Figure 6A , a8 and a9 ).…”
Section: Resultsmentioning
confidence: 99%
“…EMT is a dynamic process that affects many malignancies, including drug resistance. Accumulating evidence has highlighted that EMT has long been associated with acquired resistance to EGFR-TKIs in NSCLC [ 19 , 20 , 21 , 22 ], but the mechanisms underlying the acquired resistance to EGFR-TKIs dependent on EMT remained poorly understood. In the present study, an erlotinib-resistant HCC827/ER cell line was established by treating EGFR-mutated HCC827 cells with increasing doses of erlotinib until resistance was achieved at 5 μM erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, FGFR signaling has been associated with resistance to EGFR-TKIs caused by EMT [ 30 , 31 , 32 ]. By blocking both EGFR and FGFR, acquired resistance can be inhibited through blocking of the development of EMT in NSCLC with EGFR mutations [ 22 , 31 ]. In this study, we found that FGFR signaling was activated, resulting in acquired resistance of HCC827/ER cells and HCC827/sh LMNA cells to erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…ALK is overexpressed in ovarian cancer and associated with an aggressive, metastatic phenotype [44,45]. Finally, FRS2 inhibition could also be suitable as a combinatorial therapy strategy in KRAS-driven tumors with acquired MEKi resistance, which are sensitive to FRS2 depletion [46], or to bypass FGFR-driven resistance to epidermal growth factor receptor (EGFR) [47] or mesenchymal epithelial transition (MET) inhibition [48].…”
Section: Discussionmentioning
confidence: 99%